(untitled) (Raparin Journal of Humanities (RJH), 2025)
Climate is one of the most important geographical factors that directly and indirectly affects the activities of bees, honey production and the distribution of bees in Rwandz district. Bees thrive in good weather conditions. The higher the actual sunny hours, the better for bees as the bees work during the day, so in the study area, spring and summer, which are the growing seasons for bees, are fairly encouraging for bees to work. Temperature has a huge impact on bees, so as the temperature drops and the temperature rises, it has the effect of reducing laying eggs by the queen bee, and the worker bees expend a lot of energy to heat and cool the inside of the beehive. The low temperature in winter and the summer season due to the high temperatures bring the activity and work of the bees to a certain extent, the amount of humidity at the end of the winter season damages the beehives and hives, especially in closed boxes and crowded bees. Precipitation affects the growth of plants that are the food source of bees, flowers and plants. Precipitation has a negative effect, especially during the period of rainfall for several days in a row during the bees working season, when the natural nectar is washed away and the bees are unable to work and raise the larva. The bees often die of starvation, but in general, it does not have a negative effect on the bees. There are 192 beekeepers in the study area and the number of beehives reaches 6192 that are distributed in 29 different places and their total honey production reaches 51579.36 kg, which has a high economic value for beekeepers.